Pengaruh Kepuasan Kerja, Komitmen, Dan Budaya Organisasi terhadap Organizational Citizenship behaviour (OCB) - Michael Trisna Putra; Mintarti Indartini; Ahadiati Rohmatiah (Universitas Merdeka Madiun, 2024)
This study aims to determine the effect partially and simultaneously on Job Satisfaction, Commitment and Organizational Culture on Organizational Citizenship Behavior of employees of PT Pos Indonesia branch of Madiun City. The population in this study were employees of PT Pos Indonesia Madiun branch during the study period, totaling 60 people. Sampling using saturated sample technique. The research instrument used a questionnaire. Data analysis techniques used the classical assumption test, multiple linear regression analysis, analysis of the coefficient of determination, and hypothesis testing using the t test and F test. The results showed that partially the Commitment and Organizational Culture variables had an effect on the Organizational Citizenship Behavior of employees of PT Pos Indonesia branch of Madiun City. While the variable job satisfaction partially does not affect Organizational Citizenship Behavior on employees of PT Pos Indonesia branch of Madiun City. Simultaneously Job Satisfaction, Commitment and Organizational Culture have an effect on Organizational Citizenship Behavior of West District Office Employees.